OMIC-02. COGNITIVE DEFICITS AND ALTERED FUNCTIONAL BRAIN NETWORK ORGANIZATION IN PEDIATRIC BRAIN TUMOR PATIENTS. (1st June 2021) - Seitzman, Benjamin; Anandarajah, Hari; McMichael, Alana; Gu, Hongjie; Barbour, Dennis; Limbrick, David; Shimony, Joshua; Rubin, Joshua; Perkins, Stephanie
Abstract: Pediatric brain tumor survivors experience significant cognitive sequelae from their diagnosis and treatment. The exact mechanisms of cognitive injury are poorly understood, and validated predictors of long-term cognitive outcome are lacking. Large-scale, distributed brain systems provide a window into brain organization and function that may yield insight into these mechanisms and outcomes. We evaluated functional network architecture, cognitive performance, and brain-behavior relationships in pediatric brain tumor patients. Patients ages 8–18 years old with diagnosis of a brain tumor underwent awake resting state functional Magnetic Resonance Imaging during regularly scheduled clinical visits and were tested with the National Institutes of Health Toolbox Cognition Battery. Age- and sex-matched typically developing children were used as controls. We observed that functional network organization was significantly altered in patients compared to controls ( p < 0.001), with the integrity of the dorsal attention network particularly affected ( p < 0.0001). Moreover, patients demonstrated significant impairments in multiple domains of cognitive performance, including attention ( p < 0.0001). Finally, a significant amount of variance (R squared = 0.52, F = 3.2, p < 0.05) of age-adjusted total composite scores from the Toolbox was explained by changes in segregation between the dorsal attention and default mode networks. Our results suggest that changes in functional network organization may provide insight into long-term changes in cognitive function in pediatric brain tumor patients.